PENGARUH METODE LATIHAN SMALL SIDE GAMES DAN LATIHAN RONDO TERHADAP AKURASI PASSING PADA EKSTRAKULIKULER FUTSAL MTSN 2 TAPIN - M. Ridha Ansyari; Ramadhan Arifin; M. Mulhim (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2024)
The purpose of this study was to find out how small side games and rondo exercises affect the passing accuracy of MTSN 2 Tapin futsal extracurricular players. The research scheme used in this study is "Two Group Pre-test and Post-test Design" which uses experimental methods. The sample in this study used purposive sampling with 14 people divided into two exercise groups, namely small side games and rondo. The research instrument uses the development of a test measuring football playing skills adopted from irianto 1995. Values of 0.001 < 0.05 were obtained for the SSG group, while 0.000 < 0.05 were obtained for the rondo group values. From the difference in the average posttest score of the two groups, which was 0.28, small side games exercises were higher than rondo exercises with a ratio of 7.41 > 7.14. The findings of this study suggest both exercises used in this study had an impact on passing accuracy. However, the impact of the SSG group was greater than Rondo's training on MTSN 2 Tapin futsal extracurricular players.